2017
DOI: 10.1016/j.ijscr.2017.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of intimal sarcoma of peripheral veins

Abstract: HighlightsIntimal sarcoma is an extremely rare group.Intimal sarcoma of large veins even rarer information and case reports are limited.Unique case in the medical literature and the best current evidence in the biological behavior and the response of the multiple options of treatment in this type of tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…[6] The incidence of intimal sarcoma of pulmonary artery has been reported to be nearly twice of the aorta, primarily involving the proximal end of the blood vessel. [1] So far, approximately 200 intimal sarcoma cases have been reported. In a review of studies in the last 10 years, apart from the report by Afzal et al, only 1 article published by Zhang et al in 2019 reported a 66-year-old case who developed high-grade undifferentiated intimal sarcoma that extended from IVC with involvement of nearly whole right atrium, venae iliaca communis and bilateral renal vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] The incidence of intimal sarcoma of pulmonary artery has been reported to be nearly twice of the aorta, primarily involving the proximal end of the blood vessel. [1] So far, approximately 200 intimal sarcoma cases have been reported. In a review of studies in the last 10 years, apart from the report by Afzal et al, only 1 article published by Zhang et al in 2019 reported a 66-year-old case who developed high-grade undifferentiated intimal sarcoma that extended from IVC with involvement of nearly whole right atrium, venae iliaca communis and bilateral renal vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Intimal sarcoma is non-myogenic sarcoma originating from the tunica intima or related with large blood vessels. [1] It has been reported that intimal sarcoma accounts for only 1% of all sarcomas, which is commonly seen in aorta and pulmonary artery, but are rare in inferior vena cava (IVC). [2] It occurs mostly in older age groups, with an average age at diagnosis of 48 years for pulmonary intimal sarcoma patients and 62 years old for subjects with peripheral large veins or aortic intimal, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The primary sarcomas of the major blood vessels can be divided into three categories based on their site of origin: (a) the pulmonary artery (PA), (b) the aorta and its branches, and (c) the large veins (extremely rare group) . ISs, nonmyogenic sarcomas derived from the intima, are typically seen in the arterial system, particularly the PA, and are exceedingly rare in the IVC .…”
Section: Discussionmentioning
confidence: 99%